Fabrication of modular hyaluronan-PEG hydrogels to support 3D cultures of hepatocytes in a perfused liver-on-a-chip device. (27th December 2018) - Christoffersson, Jonas; Aronsson, Christopher; Jury, Michael; Selegård, Robert; Aili, Daniel; Mandenius, Carl-Fredrik
Abstract: Liver cell culture models are attractive in both tissue engineering and for development of assays for drug toxicology research. To retain liver specific cell functions, the use of adequate cell types and culture conditions, such as a 3D orientation of the cells and a proper supply of nutrients and oxygen, are critical. In this article, we show how extracellular matrix mimetic hydrogels can support hepatocyte viability and functionality in a perfused liver-on-a-chip device. A modular hydrogel system based on hyaluronan and poly(ethylene glycol) (HA-PEG), modified with cyclooctyne moieties for bioorthogonal strain-promoted alkyne-azide 1, 3-dipolar cycloaddition (SPAAC), was developed, characterized, and compared for cell compatibility to hydrogels based on agarose and alginate. Hepatoma cells (HepG2) formed spheroids with viable cells in all hydrogels with the highest expression of albumin and urea in alginate hydrogels. By including an excess of cyclooctyne in the HA backbone, azide-modified cell adhesion motifs (linear and cyclic RGD peptides) could be introduced in order to enhance viability and functionality of human induced pluripotent stem cell derived hepatocytes (hiPS-HEPs). In the HA-PEG hydrogels modified with cyclic RGD peptides hiPS-HEPs migrated and grew in 3D and showed an increased viability and higher albumin production compared to when cultured in the other hydrogels. This flexible SPAAC crosslinked hydrogel system enabled fabrication of perfused 3D cell culture of hiPS-HEPs and is a promising material for further development and optimization of liver-on-a-chip devices.